2017
DOI: 10.1038/s41598-017-18306-w
|View full text |Cite
|
Sign up to set email alerts
|

Beta oscillations in major depression – signalling a new cortical circuit for central executive function

Abstract: This study aimed to examine alterations in electroencephalography (EEG) phase synchronization in working memory processing in depressed patients. Sixty-four-channel EEG signals were recorded from 33 depressed patients and 32 healthy controls during a visual n-back task. Alterations in functional connections in the patients were investigated using event-related phase coherence in terms of the phase synchronization index (PSI). Compared with the control subjects, the depressed patients showed a lower task-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…The top part of Figure 4 indicates that the amplitude of the alpha rhythm (especially at approximately 10 Hz) of normal control and medicated depressive patient samples is greater than that of unmedicated depressive patients. This result is congruent with the previous findings that demonstrated that depressed patients showed a task-dependent decrease in alpha, and beta oscillations in centro-parieto-occipital sites [30], [32], [33]. The bottom part of Figure 4 demonstrates that the primary power of four rhythms of normal controls is focused on the PFC region, while the primary power of four rhythms of the medicated group and the unmedicated group is focused on bilateral frontal or parietal regions.…”
Section: ) Analysis Of the Features Learned By The Last Fully Connecsupporting
confidence: 91%
See 1 more Smart Citation
“…The top part of Figure 4 indicates that the amplitude of the alpha rhythm (especially at approximately 10 Hz) of normal control and medicated depressive patient samples is greater than that of unmedicated depressive patients. This result is congruent with the previous findings that demonstrated that depressed patients showed a task-dependent decrease in alpha, and beta oscillations in centro-parieto-occipital sites [30], [32], [33]. The bottom part of Figure 4 demonstrates that the primary power of four rhythms of normal controls is focused on the PFC region, while the primary power of four rhythms of the medicated group and the unmedicated group is focused on bilateral frontal or parietal regions.…”
Section: ) Analysis Of the Features Learned By The Last Fully Connecsupporting
confidence: 91%
“…This result might indicate prefrontal cortex abnormalities in clinically depressed subjects. Many previous studies [33]- [35] have shown that the PFC region is a significant nerve center of thinking and behavior regulation in the brain and is emerging as likely being directly involved in clinical depression.…”
Section: ) Analysis Of the Features Learned By The Last Fully Connecmentioning
confidence: 99%
“…Additionally, there have been reports of increased parietotemporal alpha coherence [83, 84] and cortical synchrony within the brains of MDD subjects [85]. A reduction in alpha synchronization in the frontoparietal network of individuals with MDD has also been shown, which may directly contribute to impaired short-term memory retention [84].…”
Section: Aberrant Network Function In Major Depressive Disordermentioning
confidence: 99%
“…In previous report, impaired memory and attention efficiency abnormally enhanced beta activity containing more short-range frontal connections as well as inter-hemispheric temporo-parietal connections in people with depression. This adaptive compensatory mechanism is also reflected in the deterioration of flexibility in cognitive control ( 30 ).…”
Section: Discussionmentioning
confidence: 99%